Study on the Bacterial Communities of the Biofilms on Titanium, Aluminum, and Copper Alloys at 5,772 m Undersea in Yap Trench - Zhai, Xiaofan; Cao, Wei; Zhang, Yimeng; Ju, Peng; Chen, Juna; Duan, Jizhou; Sun, Chengjun (Frontiers in Microbiology, 2022)
Biofilms formed on metal surfaces strongly affect metallic instruments serving in marine environment. However, due to the sampling difficulty, few has been known about the bacterial communities of the biofilm on metallic surfaces in hadal environments. So, the failure process of these deep-sea metallic instruments influenced by microbial communities could be hardly predicted. In this research, seven alloys, including titanium, aluminum and copper alloys were exposed in Yap Trench hadal environment for 1 year, thus the communities of the biofilms formed on metallic surfaces at 5772 m undersea in Yap Trench was initialy reported rather than previous studies. The 16S rRNA gene sequencing was performed to visualize the in situ bacterial communities of the biofilms formed on titanium, aluminum and copper alloys at 5772 m undersea in Yap Trench. It was found that Proteobacteria was the dominant phylum in all samples but distinct genera were discovered on various alloys. Titanium alloy provided suitable substrate for a mutualistic symbiotic biofilm with abundant bacterial richness. Aluminum alloys without copper components showed the least bacterial richness and formed cold-adapted and oligotrophic-adapted biofilm containing genera Sulfurimonas and PS1 Clade. While copper-present alloys showed relatively high bacterial richness with copper-resistant or even copper-utilizing biofilms constituted of genera Stenotrophomonas, Burkholderia-Caballeronia-Paraburkholderia and Achromobacter on the surfaces. Furthermore, among all the element component contained in alloys investigated in this research, copper element showed the strongest influences on the composition and function of microbial communities in the biofilms formed on various metallic surfaces.